Crossing the line: vagrancy, homelessness and social displacement in Russia - Stephenson, Svetlana (Ashgate, 2006)
Homeless people and urban social space -- Street society -- The process of homelessness -- Homelessness in the Soviet Union -- Soviet outcasts: displacement, expulsion and self-expulsion -- The causes of homelessness in post-Soviet Russia -- Individual paths into homelessness -- Homelessness and regulation of social space